District heating guide - Phetteplace, Gary E. (ASHRAE, 2013)
"Guidance for district heating system planning, design, operation, and maintenance for inexperienced designers and complete reference for those immersed in district heating industry; includes terminology for district heating"-- Provided by publisher.
"RP-1267."
Title from title screen.
Keywords: Heating from central stations -- Handbooks, manuals, etc.; elektronické knihy; electronic books